Focus on reflective competence: A triangulation to examine youth soccer coaches' reflective competence - Max Danner; Mareike Ahns; Günter Amesberger (Bern Open Publishing, 2024)
Introduction & Purpose Coaching is recognized as a complex socio-educational interaction (Jones, 2007), a view supported by the German Football Association (DFB). The DFB emphasizes reflection in the development of football coaches, seeing it as essential for the quality of coaching and the holistic development of youth players. Reflective competence (RC) is seen as a key component of professionalization (DFB, 2022), defined as the ability and willingness to comprehensively deal with one's own knowledge and actions in breadth and to achieve a certain depth in the reflexive and transformative engagement with issues (Krieg & Kreis, 2014). Studies show that coaches learn primarily through observation and experience (Cushion, et al., 2012), which risks perpetuating outdated behaviors. Against this background, our study asks: What (breadth) and how (depth) do youth coaches reflect on their knowledge and coaching practice? Method Seven coaches from DFB selection centers in Bavaria participated in the study. Their training sessions were videotaped and used for reflection in stimulated recall interviews (Dempsey, 2010). Coaches were asked about their understanding of reflection using narrative prompts and to reflect independently on their training sessions using the video sequences. Analysis included categorizing the understanding and relevance of reflection, as well as the breadth and depth of reflection, taking into account individual differences. Result Coaches understood reflection as "thinking about oneself" or "looking back" to consciously justify or improve practices. They showed a high level of willingness to reflect, especially valuing peer feedback. In terms of breadth, coaches mostly reflected on corrective feedback behaviors, error patterns, or training alternatives. However, the depth of reflection was limited; coaches often moved to transformative reflection without deeply analyzing issues, lacking detailed descriptions against related assumptions, previous experiences, or theoretical explanations. Discussion Coaches focused primarily on optimizing practices rather than examining issues in depth. The breadth of reflection is consistent with the DFB's shift from coach-dominated to player-dominated training practices. Conclusion Our study highlights the critical role of reflection in the professional development of youth soccer coaches at DFB selection centers in Bavaria. While coaches show a significant willingness to engage in reflective practices, there is a notable deficiency in the depth of their reflection. This highlights the need for enhanced reflective training programs that encourage deeper, more comprehensive engagement with coaching practices and theoretical knowledge. By fostering such reflective competence, coaches can contribute to a more nuanced and effective coaching methodology, ultimately benefiting the holistic development of youth players. References Cushion, J., Ford, P., & Williams, M. (2012). Coach behaviours and practice structures in youth soccer: Implications for talent development. Journal of Sports Sciences, 30(15), 1631-1641. https://doi.org/10.1080/02640414.2012.721930 Dempsey, N. P. (2010). Stimulated recall interviews in ethnography. Qualitative Sociology, 33(3), 349-367. https://doi.org/10.1007/s11133-010-9157-x Deutscher Fußball Bund. (05.02.2022). DFB-Akademie startet mit neuem Ausbildungskonzept. https://www.dfb.de/news/detail/dfb-akademie-startet-mit-neuem-ausbildungskonzept-236675/ Jones, R. L. (2007). Coaching redefined: An everyday pedagogical endeavour. Sport, Education and Society, 12(2),159-173. https://doi.org/10.1080/13573320701287486 Krieg, M., & Kreis, A. (2014). Reflexion in Mentoringgesprächen - Ein Mythos? [Reflection in mentoring discussions - A myth?] Zeitschrift für Hochschulentwicklung, 9(1),103-117. https://doi.org/10.3217/zfhe-9-01/11